Gambaran Tingkat Pengetahuan dan Sikap Remaja Tentang Pencegahan Diabetes Melitus - Sari, NI Made Candra Citra; Noviana Sagitarini, Putu; Kadek Nuryanto, I (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Diabetes mellitus is a non-communicable disease whose prevalence continues to increase worldwide, including in Indonesia. The increase in diabetes cases at a young age is a particular concern because it is related to unhealthy lifestyles since adolescence. Lack of knowledge and attitudes about prevention among adolescents has the potential to increase the risk of diabetes in the future. This condition emphasizes the importance of understanding the description of adolescents' knowledge and attitudes about diabetes mellitus prevention as a basis for developing health education programs in schools. Methods: This study used a descriptive design with a cross-sectional approach which was conducted in September 2025. The study population was 563 students in grades VIII and IX with a sample of 233 respondents taken using stratified random sampling technique. Data collection was carried out using a structured questionnaire, then analyzed univariately to see the frequency distribution of adolescents' knowledge and attitudes about diabetes mellitus prevention. Results: The study showed that most respondents were aged 13–14 years (84.6%) and female (55.1%). The level of knowledge of adolescents regarding diabetes mellitus prevention was mostly in the low category with 107 respondents (45.8%), while the majority of adolescents' attitudes towards diabetes mellitus prevention were in the poor category with 222 respondents (95.1%). Conclusion: Adolescents' knowledge and attitudes towards diabetes mellitus prevention are still relatively low. This low level of knowledge and attitudes indicates the need for targeted and sustainable health education in the school environment to raise adolescents' awareness in implementing a healthy lifestyle from an early age.